1864 Idaho Sess. Laws 634 - (:unkn) unknown (My University, 1864)
To Incorporate the City of Idaho in Boise County, § 5: Granted the mayor and common council the power and authority to regulate storage of gunpowder and other combustible materials.
Keywords: GUNPOWDER - STORAGE